2009
DOI: 10.1016/j.joca.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptome analysis of intraarticular lesional vs intact cartilage reveals new candidate genes in osteoarthritis pathophysiology

Abstract: The optimized methodical approach reported here not only allows to determine area-specific gene expression profiles of intraindividually different low-RNA containing OA cartilage specimens. In addition, this study also revealed novel genes not yet reported to play a role in the pathophysiology of joint destruction in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 40 publications
7
90
0
Order By: Relevance
“…These observations are consistent with the inhibition of periostin expression by inorganic phosphate as described previously [29]. Finally, it is of interest to report the expression of periostin in fibroblast-like synoviocytes from rheumatoid arthritis [30] and in cartilage biopsies from osteoarthritis patients [31].…”
Section: Periostin Is Expressed In Bone and Teethsupporting
confidence: 88%
“…These observations are consistent with the inhibition of periostin expression by inorganic phosphate as described previously [29]. Finally, it is of interest to report the expression of periostin in fibroblast-like synoviocytes from rheumatoid arthritis [30] and in cartilage biopsies from osteoarthritis patients [31].…”
Section: Periostin Is Expressed In Bone and Teethsupporting
confidence: 88%
“…Also, transcriptomic data obtained by Geyer and colleagues have shown that ANGPTL4 is up-regulated in damaged cartilage of a subset of osteoarthritic patients (see supplementary data in Ref. 40). In addition, ANGPTL4 was shown to stimulate osteoclast-mediated bone resorption (41).…”
Section: Discussionmentioning
confidence: 99%
“…To date, such comparisons are few and often limited in terms of using small data sets or reliant on animal models 12e17 , although several studies have examined gene expression changes between damaged and intact cartilage within the same knee joint of OA patients 13,16 . One of the first studies to compare human normal vs OA cartilage identified a decrease in expression of important oxidative defence genes especially SOD2 and SOD3 18 , a finding we recently verified 19 .…”
Section: Introductionmentioning
confidence: 99%